Bundesagentur für Arbeit: Beitragssatz senken! - Alfred Boss (Kiel Institute for the World Economy (IfW), 2017)
Die Bundesagentur für Arbeit erwirtschaftet seit Jahren erhebliche Überschüsse. Ihre Rücklagen beliefen sich Ende 2016 auf 11 Mrd. Euro. Die Überschüsse sind struktureller Art, nicht konjunkturbedingt. Der Beitragssatz sollte rasch von 3 auf 2,7 Prozent gesenkt werden. So ließen sich der Anstieg der gesamten Belastung durch Sozialversicherungsbeiträge und die Zunahme der Arbeitskosten, zu denen es Anfang 2017 kam, rückgängig machen - mit positiven Folgen für die Beschäftigung. – – In Germany, the system of unemployment insurance has been in surplus since 2011. The reserves amounted to Euro 11 bn in the end of 2016. Only a small part of the surplus is due to the cyclical stance of the German economy. The surplus mainly is a structural one. The rate of contribution to unemployment insurance should be reduced from 3 to 2.7 percent soon. This would avoid an increase of the overall rate of contributions to social security in 2017. The increase of employment would be fostered.
Keywords: 330